DOA BERSAMA DALAM KELUARGA SEBAGAI SARANA PENDIDIKAN IMAN ANAK - Euvemia Erma; Ola Rongan Wilhemus (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Praying together in family is a prayer offered together by the parents with all their children. Parents have a responsibility as the first and primary educator for their children. Parents carry out praying together in the family as a means to educate the children to be more faithful to God. In fact, the christian family seldom pray together, because of the various reasons of each member of the family. This scientific research h used the qualitative research method which directed to answer the research question: (1) What is the meaning and the function of praying in daily life? (2) What is the meaning and the benefit of praying together in a family? (3) How is the frequency of praying together in the family? (4) What kind of prayers are usually done in the family? (5) What is the impact of praying together in the family for the development of the children's faiths? The result of the research in general shows that the respondents have understood the meaning, the function and the benefit of the prayer in daily life. However 50% of the respondents seldom pray together in the family. The respondents knew that praying together in their family can be the means of the children's faith education. Therefore prayer becomes something very important and can't be ignored. The more often families established prayer together, the greater the influence on the spiritual growth of children.